2012
DOI: 10.1161/strokeaha.111.643296
|View full text |Cite
|
Sign up to set email alerts
|

Depression Screening in Stroke

Abstract: Background and Purpose— Screening tools for depression and psychological distress commonly used in medical settings have not been well validated in stroke populations. We aimed to determine the accuracy of common screening tools for depression or distress in detecting caseness for a major depressive episode compared with a clinician-administered structured clinical interview for Diagnostic and Statistical Manual of Mental Disorders Fourth Edition as the gold standard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 35 publications
0
38
1
1
Order By: Relevance
“…Similar to previous studies, the majority of participants reported unsatisfactory levels of vegetable and fruit consumption, physical activity and alcohol consumption. Anxiety and depression was markedly low in our sample compared to previous literature, 4,5 with only one participant reporting severe psychological distress. Quality of life was consistent with previous literature, in which stroke survivors have reported problems with mobility, pain/discomfort and difficulty engaging in their usual activities.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Similar to previous studies, the majority of participants reported unsatisfactory levels of vegetable and fruit consumption, physical activity and alcohol consumption. Anxiety and depression was markedly low in our sample compared to previous literature, 4,5 with only one participant reporting severe psychological distress. Quality of life was consistent with previous literature, in which stroke survivors have reported problems with mobility, pain/discomfort and difficulty engaging in their usual activities.…”
Section: Discussioncontrasting
confidence: 72%
“…The program also consists of a loading survey and goals module, which is tailored to the user and provides self‐management opportunities. P2S provides evidence‐based information and strategies that can help to reduce the risk of having another stroke as well as advice on addressing anxiety and depression 5 . The program incorporates behaviour change techniques, 24 such as goal setting and feedback on progress, and is also tailored to encourage positive behaviour change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cut-off point at 11 has been used in previous studies in stroke population. This cut-off has a good sensitivity and specificity for the detection of depression after a stroke (Turner et al, 2012; Kang et al, 2013). …”
Section: Methods and Analysismentioning
confidence: 99%
“…However, studies on PSD have primarily focused on exploring its prevalence, pathogenic factors as well as treatment 37. Only a few researchers have pursued the psychopathology and diagnosis of depression after stroke 8,9. Like other psychiatric disorders, the diagnostic nosology was compelled to focus on clinical manifestations, duration and function disrupted due to ambiguous etiology.…”
Section: Introductionmentioning
confidence: 99%